Lactobacillus acidophilus ATCC 4356 Alleviates Renal Ischemia–Reperfusion Injury Through Antioxidant Stress and Anti-inflammatory Responses and Improves Intestinal Microbial Distribution - Zhang, Peng; Han, Xiuwu; Zhang, Xin; Zhu, Xuhui (Frontiers in Nutrition, 2021)
Background: Ischemia-reperfusion injury (IRI) is one of the main causes of acute kidney injury. Our previous results have shown that the anti-oxidative stress decreased in the renal IRI model. This study aimed to investigate the effect of Lactobacillus acidophilus ATCC4356 on oxidative stress, inflammation and intestinal flora in renal IRI. Methods: The model of renal IRI was established by cross-clamping the renal pedicle with nontraumatic vascular forceps. HE staining was applied to observe the damage of kidney tissue in each group. The concentration of serum BUN, Cre, SOD, GSH, MDA were detected by biochemical kit. ELISA measured the concentration of IL-1β, IL-8, IL-4, IL-10. qRT-PCR was performed to detect molecular expression of ATCC 4356, oxidative stress related factors (NRF2, HO-1), inflammatory factors (TNFα, IL-1β, IL-8, IFN-γ, IL-4, IL-10), apoptosis related factors (Caspase3, Bax, Bcl2, HMGB1). Except for ATCC 4356, the protein expression of the above indicators was detected by Western blot. The apoptosis level of renal tissue cells was detected by TUNEL. 16S rDNA gene sequencing was used to detect the expression of microbial changesspecies in intestinal tissue contents of duodenum, and screen out the differentially expressed flora. Results: Both the glomeruli and renal tubules of I/R mice were severely damaged. HE result displayed that Lactobacillus acidophilus ATCC 4356 attenuated the damage and the infiltration of inflammatory cells caused by I/R. ATCC 4356 reduced the high expression of BUN and CRE in I/R mice with a dose effect. It also reduced the high expression of MDA, TNFα, IL-1β, IL-8, IFN-γ, caspase3, Bax and HMGB1 in I/R mice, while increased low expression of SOD, GSH, NRF2, HO-1, IL-4, IL-10, and Bcl2 in I/R mice. ATCC 4356 inhibited the high level of apoptosis in the kidney tissue of I/R mice. The 16S rDNA results showed that compared with normal mice, The top three differences in gut microbiota were helicobacter, cultivated_ bacterium, k__ Bacteria_ ASV_ 3 in IRI mice, and oral Lactobacillus acidophilus ATCC 4356 reversed this change. Conclusion: Lactobacillus acidophilus ATCC 4356 attenuated renal IRI through anti-oxidative stress and anti-inflammatory response, and improved the intestinal microbial distribution.